The effect of intrahepatic cholestasis in pregnancy combined with different stages of hepatitis B virus infection on pregnancy outcomes: a retrospective study - Qian Gao; Xuejiao Li; Li Wang; Xiaozhi Tan; Zhe Li; Chengfang Xu (BMC, 2024)
Abstract Background and aims To investigate the impact of intrahepatic cholestasis of pregnancy (ICP) with hepatitis B virus (HBV) infection on pregnancy outcomes. Methods We selected 512 pregnant women, collected the data including maternal demographics, main adverse pregnancy outcomes and maternal HBV infected markers HBeAg and HBV-DNA loads status, then have a comparative analysis. Results There were 319 solitary ICP patients without HBV infection (Group I) and 193 ICP patients with HBV infection. Of the latter, there were 118 cases with abnormal liver function(Group II) and 80 cases with normal liver function(Group III). All HBV-infected pregnant women with ICP were divided into hepatitis Be antigen (HBeAg)-positive group (102 cases) and HBeAg-negative group (91 cases), according to the level of the serum HBeAg status; and into high viral load group (92 cases), moderate viral load group (46 cases) and low viral load group (55 cases) according to the maternal HBV-DNA level. Group II had a higher level of serum total bile acids, transaminase, bilirubin as well as a higher percentage of premature delivery, neonatal intensive care unit (NICU) admission and meconium-stained amniotic fluid (MSAF) compared with the other two groups(P < 0.05), but there were no significant differences in the above indicators between the Group I and Group III. Among the HBV-infected patients with ICP, HBeAg-positive group had a higher level of serum transaminase, bilirubin and bile acid as well as earlier gestational weeks of delivery, lower birth weight of new-borns and a higher rate of NICU admission than HBeAg-negative group (P < 0.05). Those with a high viral load (HBV-DNA > 106 IU/ml) had a higher level of transaminase, bilirubin, and bile acid as well as shorter gestational weeks of delivery, lower birth weight of new-borns and a higher rate of NICU admission compared with those with a low or moderate viral load (P < 0.05). Conclusion HBV-infected pregnant women with ICP combined with abnormal liver function have more severe liver damage, a higher percentage of preterm birth and NICU admission. HBeAg-positive status and a high HBV-DNA load will increase the severity of conditions in HBV-infected pregnant women with ICP. HBV-infected patients with ICP who have abnormal liver function, HBeAg-positive or a high viral load should be treated more actively.